2013
DOI: 10.1371/journal.pone.0055207
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Transcriptional Changes in ERG Rearrangement-Positive Prostate Cancer Identifies the Regulation of Metabolic Sensors Such as Neuropeptide Y

Abstract: ERG gene rearrangements are found in about one half of all prostate cancers. Functional analyses do not fully explain the selective pressure causing ERG rearrangement during the development of prostate cancer. To identify transcriptional changes in prostate cancer, including tumors with ERG gene rearrangements, we performed a meta-analysis on published gene expression data followed by validations on mRNA and protein levels as well as first functional investigations. Eight expression studies (n = 561) on human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 72 publications
(77 reference statements)
2
38
0
Order By: Relevance
“…We also investigated metabolic pathways connected to glycine and glucose metabolism, as TMPRSS2-ERG has been suggested to be linked to increased glucose uptake [17, 18]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated metabolic pathways connected to glycine and glucose metabolism, as TMPRSS2-ERG has been suggested to be linked to increased glucose uptake [17, 18]. …”
Section: Resultsmentioning
confidence: 99%
“…Citrate and spermine, including choline and creatine are metabolites detectable by in vivo patient magnetic resonance spectroscopy imaging (MRSI), which imply a potential for transferring biomarkers to a clinical setting [16]. A recent study revealed ERG-specific metabolic alterations, particularly connected to fatty acid oxidation [17] and an earlier study found increased glucose uptake to be related to the metabolic sensor neuropeptide gamma ( NPY ) in ERG rearrangement positive prostate cancer [18]. Apart from these two studies, the relationship between cancer metabolism and TMPRSS2-ERG remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…ECE1 has been implicated in prostate cancer cell invasion, in which different isoforms of the protein were found to play different roles (19). PLA2G4C is regulated by EGR, a gene that is rearranged in approximately 50% of prostate cancer (20). In bladder cancer, very few of the top findings have been published in association with disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we analysed data of a PCa meta-analysis study which we performed previously (Massoner et al , 2013). …”
Section: Methodsmentioning
confidence: 99%